RELIGIUSITAS DALAM RITUAL AROHA DI PELAUW - Yance Z. Rumahuru (Jurnal Studi Islam, 2020)
This article aims to explain in a ritualistic religiosity Aroha, a typical ritual Muslim community in the State Hatuhaha Pelauw Haruku Island District of Central Maluku district to honor the Prophet Muhammad, Islam ancestors and broadcasters. It is assumed that there is an attitude in the ritual religiosity into a wealth of traditions and diversity of religious practices of Islam in Indonesia. This paper is built from the author's observation on the implementation of ritual Aroha in 2011 and interviews with several informants in Pelauw State. Analysis of the implementation of these rituals using interpretation models developed by Clifford Geertz. Encountered that first, the implementation of Aroha is a moment to evaluate the behavior of any person or citizens of the country or the people, and fix it in everyday life, which in this study is understood as part of the local community religiosity. Second, Aroha becomes effective in order to understand the dialectic of tradition and religion, as in the implementation of Aroha each person carrying out the teaching of religion and custom together, and make the values Aroha as a guide in building individual and group life. In this regard Aroha has the meaning "purification" or "born again", and can be also related with the tradition of forgiveness or atonement in religious practices in general.